2016
DOI: 10.1155/2016/1936386
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autophagy-Related Protein and Cell Differentiation by High Mobility Group Box 1 Protein in Adipocytes

Abstract: High mobility group box 1 protein (HMGB1) is a molecule related to the development of inflammation. Autophagy is vital to maintain cellular homeostasis and protect against inflammation of adipocyte injury. Our recent work focused on the relationship of HMGB1 and autophagy in 3T3-L1 cells. In vivo experimental results showed that, compared with the normal-diet group, the high-fat diet mice displayed an increase in adipocyte size in the epididymal adipose tissues. The expression levels of HMGB1 and LC3II also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…
Proper regulation of food intake can be disrupted by sustained metabolic challenges such as high-fat diet (HFD), which may result in various metabolic disorders. Previously, we showed that starvation induced sustained hyperactivity, an exploratory component of food-seeking behavior, via a specific group of octopamingeric (OA) neurons (Yu et al, 2016). In the present study, we found that HFD greatly enhanced starvation-induced hyperactivity.
…”
supporting
confidence: 58%
See 4 more Smart Citations
“…
Proper regulation of food intake can be disrupted by sustained metabolic challenges such as high-fat diet (HFD), which may result in various metabolic disorders. Previously, we showed that starvation induced sustained hyperactivity, an exploratory component of food-seeking behavior, via a specific group of octopamingeric (OA) neurons (Yu et al, 2016). In the present study, we found that HFD greatly enhanced starvation-induced hyperactivity.
…”
supporting
confidence: 58%
“…We have previously reported that starvation induced hyperactivity in fruit flies Drosophila melanogaster, which facilitated the localization and acquisition of food and hence partly resembled food-seeking behavior (Yang et al, 2015;Yu et al, 2016). In this present study, we first asked whether HFD affected starvation-induced hyperactivity in fruit flies.…”
Section: Hfd Specifically Enhanced Starvation-induced Hyperactivitymentioning
confidence: 73%
See 3 more Smart Citations